Effect of nano TiO2-epoxy composite in bond strength and corrosion resistance of rebar embedded in micro-silica modified concrete. (December 2020) - Ramganesh, V; Ananth Kumar, M; Mini, KM; Vignesh, Vaishno; Karthikeyan, R
Abstract: One of the significant drawbacks of RCC structures is Corrosion. It is a well-known term used to describe numerous interactions between a material and its surrounding environment resulting in degradation within the material properties. Reacting with ambient oxygen can cause the material to degrade by forming a more chemically stable form of oxides called Rust. A detailed literature study about the recent advances in the area of corrosion resistance of reinforced concrete has been done using nano-materials. Nano-materials can be deemed fit to be used in cement and concrete manufacture and have a wide range of applications in the civil industry. Compressive strength and ductility of concrete can be improved by blending Nano-materials in concrete. Leads to producing a very dense concrete and Decreases permeability of the concrete by micro filler effect. In the present study, nanomaterial is used in the preparation of coating material on the reinforcement bar. Higher opacity, the interaction between coating and surface, and higher durability of the coating can be achieved by adding nano-material. Different percentages of nano-TiO2 (0.5%, 1%, 2%) mixed with epoxy are varied to find the percentage, which gives the least rate of Corrosion. For this purpose, the specimens coated with nano-TiO2 epoxy composite are placed in two mediums such as 3.5% NaCl solution and 1M H2 SO4 solution and studied the performance of corrosion resistance for every 15-day interval using LPR, Tafel plot and Electrical Impedance Spectroscopy(EIS).Characteristic properties like topography, composition, and surface morphology are studied using SEM, FTIR, and XRD analysis. To increase the mechanical properties of reinforced concrete, so industrial by-product micro-silica has been added to the cement mix. Reinforced cylindrical specimens were cast and were tested for bond strength. For micro-silica replaced concrete mix, destructive tests like compressive strength test and tensile strength tests were conducted